Skew Correction and Density Detection of Knitted and Woven Fabric (Journal of Fiber Bioengineering and Informatics, 2016)
Automatic identification of fabric structure is a vital area of research. The skewing phenomenon isinevitable during the scanning process, so the fabric skew correction method based on projection profileanalysis is proposed. First, Butterworth low-pass filter is applied to remove noises after skew correction ofthe fabric image. Then, power spectrum is obtained by Fast Fourier Transform (FFT), in which the peaksare extracted from the vertical and horizontal direction, respectively. Finally, the reconstructed imageis obtained via Inverse Fast Fourier Transform (IFFT) according to the peaks, so that the informationof warp and weft can be separated to calculate the warp and weft density. Experimental results showthat the accuracy of the skew correction can be controlled within [-1°, 1°], and the detection accuracyof yarn density can reach 98%. The proposed method can accurately detect skew angle and density ofwoven and knitted fabrics.
Keywords: Skew Correction; Projection Profile Analysis; FFT; Density Detection